2008
DOI: 10.1074/jbc.m803812200
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Inhibits Sodium Transport via Down-regulation of SGK1 in Renal Collecting Duct Principal Cells

Abstract: Tubulointerstitial inflammation is a common feature of renal diseases. We have investigated the relationship between inflammation and Na؉ transport in the collecting duct (CD) using the mCCD cl1 and mpkCDD cl4 principal cell models. Lipopolysaccharide (LPS) decreased basal and aldosterone-stimulated amiloride-sensitive transepithelial current in a time-dependent manner. This effect was associated with a decrease in serum and gucocorticoid-regulated kinase 1 (SGK1) mRNA and protein levels followed by a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 44 publications
(34 reference statements)
1
38
0
Order By: Relevance
“…27,39,40 Notably, membrane expression of TGF-␤ strongly depends on cell polarization, which may explain why in the present study only cells at the edge of a monolayer expressed Best1 and proliferated, since they are able to expose their basolateral TGF-␤ receptors to serum factors. 41 Similar observations were done in a colonic carcinoma cell line (T 84 ), that changed from a polarized growth pattern to fast growing cells with augmented intracellular Ca 2ϩ signaling.…”
Section: Discussionmentioning
confidence: 76%
“…27,39,40 Notably, membrane expression of TGF-␤ strongly depends on cell polarization, which may explain why in the present study only cells at the edge of a monolayer expressed Best1 and proliferated, since they are able to expose their basolateral TGF-␤ receptors to serum factors. 41 Similar observations were done in a colonic carcinoma cell line (T 84 ), that changed from a polarized growth pattern to fast growing cells with augmented intracellular Ca 2ϩ signaling.…”
Section: Discussionmentioning
confidence: 76%
“…40,49 -51 More recently, we demonstrated in CD cells that prolonged NF-B activation inhibits transepithelial sodium transport via downregulation of SGK1 expression and subsequent decreased expression of aldosterone-induced sodium transporters. 52 Interestingly, inhibition of sodium transport by IL-1␤ is more pronounced in mineralocorticoid-than in glucocorticoid-stimulated CD cells. 40 This observation might be explained by an additional stimulation of NF-B by activated MR and by its inhibition by activated GR.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies suggest that stimulation of the IKK/NF-B pathway by either tumor necrosis factor-␣ or LPS inhibits ENaC activity, at least over relatively long time intervals (hours to days) (17,18). This inhibition may occur via down-regulation of SGK1 in renal collecting duct epithelial cells and is earliest seen at 6 h (18).…”
Section: Discussionmentioning
confidence: 99%
“…Amiloride-sensitive alveolar fluid clearance, a function of ENaC activ-ity, increases in a rat model of pneumonia by a tumor necrosis factor-␣-dependent mechanism (16). In contrast, prolonged (12-24 h) exposure of alveolar epithelial cells to tumor necrosis factor-␣ (17) or of mouse collecting duct cells to LPS (18) results in down-regulation of ENaC activity and expression. We have found that aldosterone, the major hormonal regulator of ENaC, increases IKK␤ levels in renal epithelia and activates NF-B and have suggested that long term stimulation of NF-B might represent a negative feedback loop modulating long term ENaC activation in conditions of oxidative or metabolic stress (10).…”
mentioning
confidence: 99%